2022
DOI: 10.1002/ehf2.13859
|View full text |Cite
|
Sign up to set email alerts
|

Advanced heart failure: guideline‐directed medical therapy, diuretics, inotropes, and palliative care

Abstract: Heart failure (HF) is a major cause of mortality, hospitalizations, and reduced quality of life and a major burden for the healthcare system. The number of patients that progress to an advanced stage of HF is growing. Only a limited proportion of these patients can undergo heart transplantation or mechanical circulatory support. The purpose of this review is to summarize medical management of patients with advanced HF. First, evidence‐based oral treatment must be implemented although it is often not tolerated.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
41
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 41 publications
(49 citation statements)
references
References 119 publications
2
41
0
Order By: Relevance
“…321 The efficacy and tolerability of GDMT in patients with the most advanced stages of HFrEF often remain unsettled. 150,322,323…”
Section: Definition and Prognosismentioning
confidence: 99%
See 1 more Smart Citation
“…321 The efficacy and tolerability of GDMT in patients with the most advanced stages of HFrEF often remain unsettled. 150,322,323…”
Section: Definition and Prognosismentioning
confidence: 99%
“…The HFA‐ESC advanced HF definition was associated with a higher risk of all‐cause mortality or first HF hospitalization (adjusted HR 1.98; 95% CI 1.57–2.50; P < 0.001) 321 . The efficacy and tolerability of GDMT in patients with the most advanced stages of HFrEF often remain unsettled 150,322,323 …”
Section: Advanced Heart Failurementioning
confidence: 99%
“…Levosimendan plays a vasodilator and cardioprotective role and has been shown to be effective in improving cardiac function, relieving symptoms, and reducing mortality and hospitalization rates in patients with heart failure [28][29][30] . As for Omecamtiv mecarbil 31,32 , the completed phase II and phase III trials COSMIC-HF trial 33 , GALACTIC-HF trial 34 , and ATOMIC-AHF trial 35 have all shown a bene t of Omecamtiv mecarbil on heart failure improvement in patients with HFrEF, and for patients with LVEF < 40%. When LVEF < 28%, patients treated with Omecamtiv Mecarbil showed greater improvement in the primary end point event, and the bene t may be greater.…”
Section: Discussionmentioning
confidence: 99%
“…Medical management of patients with advanced HF remains a largely unmet clinical need 55,68–70 . Current guidelines report that long-term mechanical circulatory support (MCS) and heart transplantation have to be considered also in patients with NYHA class II at high risk for HF progression.…”
Section: Advanced Heart Failurementioning
confidence: 99%